Does the inclusion of ballistic exercises during warm-up enhance short distance running performance? - Gil, M. H.; Neiva, H. P.; Alves, A. R.; Sousa, A. C.; Duarte-Mendes, P.; Marques, M. C.; Marinho, D. A. (The Journal of Sports Medicine and Physical Fitness, 2020)
BACKGROUND: Warm-up is considered essential to optimize running performance, but little is known about the effect of specific warm-up tasks, specifically in the real competitive context. The current study aimed to verify the acute effects of a warm-up including ballistic exercises in 30m running performance. In addition, a second 30m trial was assessed to better understand the warm-up effects in training/competition. METHODS: Twenty-two men (19.32±1.43 years-old) randomly completed the time-trials on separate days and after a typical warm-up (WU), a WU complemented with ballistic exercises (postactivation potentiation [PAP]) or no warm-up (NWU). Biomechanical, physiological and psychophysiological variables were assessed. RESULTS: The participants were 1.9% faster in the first 30m sprint after WU compared with NWU, mainly increased performance in the first 15m (P=0.03, ES=0.48). WU resulted in greater stride length in the last 15m of the first sprint. PAP did not differ from NWU and WU, despite eight participants performed better after this warm-up. CONCLUSIONS: These results highlight the positive effects of warm-up for sprinting, despite failed to evidence positive effects when ballistic exercises are included. In addition, the influence of warm-up in the running technique was highlighted by the changes in the running kinematics and a need for individualization of warm-up procedures.